FCGR2/3 polymorphisms are associated with susceptibility to Kawasaki disease but do not predict intravenous immunoglobulin resistance and coronary artery aneurysms - Uittenbogaard, Paula; Netea, Stejara A.; Tanck, Michael W. T.; Geissler, Judy; Buda, Piotr; Kowalczyk-Domagała, Monika; Okarska-Napierała, Magdalena; van Stijn, Diana; Tacke, Carline E.; , US Kawasaki Disease Genetics Consortium; Burgner, David P.; Shimizu, Chisato; et al. (Frontiers in Immunology, 2024)
Introduction Kawasaki disease (KD) is a pediatric vasculitis that can result in coronary artery aneurysm (CAA) formation, which is a dangerous complication. Treatment with intravenous immunoglobulin (IVIg) significantly decreases the risk of CAA, possibly through competitive binding to Fc-gamma receptors (FcγRs), which reduces the binding of pathological immune complexes. However, 20% of children have recrudescence of fever and have an increased risk of CAA. Therefore, we aimed to identify genetic markers at the FCGR2/3 locus associated with susceptibility to KD, IVIg resistance, or CAA. Materials and methods We investigated the association of single-nucleotide polymorphisms (SNPs) and copy number variations (CNVs) at the FCGR2/3 locus with KD susceptibility, IVIg resistance, and CAA risk using a family-based test (KD susceptibility) and case–control analyses (IVIg resistance and CAA risk) in different cohorts, adding up to a total of 1,167 KD cases. We performed a meta-analysis on IVIg resistance and CAA risk including all cohorts supplemented by previous studies identified through a systematic search. Results FCGR2A-p.166His was confirmed to be strongly associated with KD susceptibility (Z = 3.17, p = 0.0015). In case–control analyses, all of the investigated genetic variations at the FCGR2/3 locus were generally not associated with IVIg resistance or with CAA risk, apart from a possible association in a Polish cohort for the FCGR3B-NA2 haplotype (OR = 2.15, 95% CI = 1.15–4.01, p = 0.02). Meta-analyses of all available cohorts revealed no significant associations of the FCGR2/3 locus with IVIg resistance or CAA risk. Discussion FCGR2/3 polymorphisms are associated with susceptibility to KD but not with IVIg resistance and CAA formation. Currently known genetic variations at the FCGR2/3 locus are not useful in prediction models for IVIg resistance or CAA risk.